2006 IEEE 12th Digital Signal Processing Workshop &Amp;amp; 4th IEEE Signal Processing Education Workshop 2006
DOI: 10.1109/dspws.2006.265466
|View full text |Cite
|
Sign up to set email alerts
|

A DSP Hardware-Based Laboratory for Signals and Systems

Abstract: Hardware-based laboratories have been successfully integrated into individual Digital Signal Processing (DSP) courses at many universities. Typically, most hardware-based DSP laboratory experiences are offered to upper-level students and focus on programming the signal processor. While this approach may be ideal for preparing motivated upper-level students for future careers in signal processing, it is not suitable for students with no prior experience in the field. To address this issue, a hardware-based sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Many such courses have already been developed for different hardware platforms, including general-purpose processors (GPPs) [1][2][3], field programmable gate arrays (FPGAs) [4,5], graphical processing units (GPUs) [6] and digital signal processors (DSPs), which are historically the first integrated circuits specially designed to solve digital signal processing tasks in real-time with low-power consumptions. The educational courses on DSP programming are described in [7][8][9][10][11]. In this paper we concentrate on multicore (DSPs).…”
Section: Introductionmentioning
confidence: 99%
“…Many such courses have already been developed for different hardware platforms, including general-purpose processors (GPPs) [1][2][3], field programmable gate arrays (FPGAs) [4,5], graphical processing units (GPUs) [6] and digital signal processors (DSPs), which are historically the first integrated circuits specially designed to solve digital signal processing tasks in real-time with low-power consumptions. The educational courses on DSP programming are described in [7][8][9][10][11]. In this paper we concentrate on multicore (DSPs).…”
Section: Introductionmentioning
confidence: 99%
“…1 Hardware-based Digital Signal Processing (DSP) laboratories have had marked success in providing hands-on, realistic lab experiences to undergraduate students in an Electrical and Computer Engineering (ECE) curriculum. 1,2,3 The development of such laboratories for a required introductory signal processing course has demonstrated that application-based exercises illustrating the fundamental signal processing concepts using a DSP hardware platform have been well received. 2 The course studied here is typically taken by sophomore or junior level students in both the ECE and Biomedical Engineering (BME) fields.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3 The development of such laboratories for a required introductory signal processing course has demonstrated that application-based exercises illustrating the fundamental signal processing concepts using a DSP hardware platform have been well received. 2 The course studied here is typically taken by sophomore or junior level students in both the ECE and Biomedical Engineering (BME) fields. In it, MATLAB software with the SIMULINK toolbox is used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…table-based laboratories 8 , and remote laboratories 9 . In a traditional "closed laboratory" environment, students perform the assignments following a "cook-book" lab manual and submit a written report drafted after the laboratory has been completed.…”
Section: Introductionmentioning
confidence: 99%